2021
DOI: 10.3389/fonc.2021.706733
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Parametric MRI-Based Radiomics Models for Predicting Molecular Subtype and Androgen Receptor Expression in Breast Cancer

Abstract: ObjectiveTo investigate whether radiomics features extracted from multi-parametric MRI combining machine learning approach can predict molecular subtype and androgen receptor (AR) expression of breast cancer in a non-invasive way.Materials and MethodsPatients diagnosed with clinical T2–4 stage breast cancer from March 2016 to July 2020 were retrospectively enrolled. The molecular subtypes and AR expression in pre-treatment biopsy specimens were assessed. A total of 4,198 radiomics features were extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 63 publications
2
38
0
Order By: Relevance
“…Comparatively, the model performance was not adequate in task 4 (training cohort: 0.697; test cohort: 0.663). The result is in agreement with a recent study by Huang et al who built ternary classification MRI-based models to predict molecular subtypes of breast cancer (accuracy, 0.623-0.735) (36). Although we incorporated the optimal peritumoral features, the performance is still unsatisfactory in the ternary classification task.…”
Section: Discussionsupporting
confidence: 90%
“…Comparatively, the model performance was not adequate in task 4 (training cohort: 0.697; test cohort: 0.663). The result is in agreement with a recent study by Huang et al who built ternary classification MRI-based models to predict molecular subtypes of breast cancer (accuracy, 0.623-0.735) (36). Although we incorporated the optimal peritumoral features, the performance is still unsatisfactory in the ternary classification task.…”
Section: Discussionsupporting
confidence: 90%
“…According to previous results, the feature selector and classifier were two major determinant factors of radiomics model performance ( 20 23 , 38 , 39 ). When a suitable classifier was used, there was no significant difference in the AUC value of different sequences.…”
Section: Discussionmentioning
confidence: 77%
“…found that the combination of radiomics and machine learning based on multi-parameter MRI provides a promising method for the non-invasive prediction of molecular subtypes and androgen receptor expression of breast cancer. The MLP classifier showed the best performance in discriminating triple-negative breast cancer (TNBC) vs. non-TNBC (AUC, 0.965; accuracy, 92.6%) ( 22 ). Choudhery et al.…”
Section: Discussionmentioning
confidence: 99%